Smak drogi. Podróże chorwackiego romantyzmu (1839–1860) - Pieniążek-Marković, Krystyna (Adam Mickiewicz University Press, 2024)
The author's main interest is Croatian travelogues, particularly those from between the years of 1839 to 1860. The starting date is the year of the publication of the first Croatian travelogue of the Romantic period (Illyrianism), whose author was Ivan Trnski, but at the same time, these mark the beginnings of Croatian Romanticism. The closing date is connected to the end of Romanticism to the end of absolutism in the years of 1851–1860). Among the best-known travel writers from 1839–1860 period are Ivan Trnski, Matija Mažuranić, Stanko Vraz, Antun Nemčić Gostovinski, Ivan Kukuljević Sakcinski, Adolfo Veber Tkalčević and the Bosnian Franciscans Grgo Martić and Ivan Frano Jukić (functioning within both Bosnian and Croatian literatures). It is to their travels that she devote her attention to, with the focus being all the travel accounts that appeared in book form during this period, Trnski’s accounts published in the press (due to their pioneering character), and also the Franciscans' travels that are important to be able to visualise a comprehensive picture of Bosnia. She therefore focus on an analysis of Croatian nineteenth-century travel writing that is representative of the time and the dominant ideologies, first of the Illyrian Movement (Revival Movement) and then that of Yugoslavism, while illustrating the geographical multi-directionality of Romantic peregrinations.